Evaluasi Sistem Jaminan Keamanan Pangan di Restoran Multicabang PT XYZ Area Jakarta - Maharani, Katarina; Rahayu, Winiati Pudji; Nurjanah, Siti (Jurnal Mutu Pangan : Indonesian Journal of Food Quality, 2023)
Improper restaurant management causes potential food safety hazards which can lead to decline in public health. This study aims to evaluate food safety system at restaurant multisite PT XYZ area Jakarta to determine the knowledge of managers and knowledge, attitudes and practices of food handler about food safety, analyze level correlation between knowledge food handlers with attitudes and practices, correlate food safety knowledge restaurant managers with E. coli contamination and also observed general food safety implementation in restaurant. Data collection was by filling out questionnaires by 136 food handlers and 44 restaurant manager and observation of food safety in 44 restaurants. The results showed that restaurant managers had good knowledge of food safety and 63.6% had attended food safety training. Food handlers had good knowledge, attitudes, and practices (77.21, 84.56, 80.15%). Statistical analysis did not indicate a significant correlation between knowledge and attitudes. However, it was found that there is correlation between knowledge with practice and attitudes with practice. Observation result of restaurant food safety implementation showed that 93.8% had a good implementation. The knowledge of restaurant managers correlated positively with the implementation of restaurant food safety practices, but did not correlate with the presence of E.coli. The presence of E.coli  did not indicate corelation  with restaurant  observation value. Testing  E.coli at 44 restaurants showed that 9 of the salad samples and 3 of the sushi samples were detected by E.coli, while the ice coffee milk did not detect E. coli.